Consciousness Energy Healing Treatment: Spectroscopic and Calorimetric Evaluation of the Biofield Energy Treated Hydroxypropyl β-Cyclodextrin - Dahryn Trivedi; Mahendra Kumar Trivedi; Alice Branton; Gopal Nayak; Snehasis Jana (Journal of New Developments in Chemistry, 2019)
Hydroxypropyl β-Cyclodextrin (HPBCD) used in food, pharmaceutical, chemical industries, as well as environmental, and agriculture engineering. But the major issue related to HPBCD is the low solubility profile. In this study, the influence of the Consciousness Energy Healing Treatment (the Trivedi Effect®) on the physicochemical properties of HPBCD was evaluated using spectroscopic and calorimetric analytical techniques. The test sample (HPBCD) was divided into control sample and treated sample. The control sample did not receive the Biofield Energy Treatment. Whereas, the treated sample received the Biofield Energy Treatment remotely by a renowned Biofield Energy Healer, Dahryn Trivedi. The particle size values of the treated sample were decreased by 3.28%(d10), 1.36%(d50), 0.45%(d90), and 1.04%D(4,3); therefore, the specific surface area was increased by 1.9% compared with the control sample. The evaporation temperature of the treated HPBCD sample was significantly decreased by 19.89%; however, the latent heat of evaporation and latent heat of fusion were significantly increased by 56.27% and 47.41%, respectively compared with the control sample.The total weight loss in the treated HPBCD was decreased by 5.11%; whereas, the residue amount was significantly 309.67% more compared to the control sample.The results indicated that the Trivedi Effect® might have produced a new form of HPBCD which may show better thermal stability, solubility, dissolution rate, and bioavailability. This new form of HPBCD would be more useful for improvement of solubility of the lipophilic drug, preparation of cholesterol free food products, weight loss supplements, anti-obesity medication, stabilize volatile and unstable compounds, and other manufacturing industry using it as a raw material.
Keywords: Hydroxypropyl β-Cyclodextrin